Mechanisms of resistance to reversible inhibitors of EGFR tyrosine kinase in non-small cell lung cancer - Krawczyk, Paweł; Mlak, Radosław; Powrózek, Tomasz; Nicoś, Marcin; Kowalski, Dariusz M.; Wojas-Krawczyk, Kamila; Milanowski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2012)
Abnormalities of epidermal growth factor receptor (EGFR) in non-small-cell lung cancer (NSCLC) patients consist of EGFR overexpression and EGFR (HER1) gene mutations. Structural dysfunction of the tyrosine kinase domain of EGFR is associated with the clinical response to tyrosine kinase inhibitors (TKI) in patients with NSCLC. The most common EGFR gene mutations occur as either deletions in exon 19 or as substitution L858R in exon 21 and cause a clinically beneficial response to gefinitib or erlotinib treatment. Unfortunately, the majority of patients finally develop resistance to these drugs. Acquired resistance is linked to secondary mutations localised in the EGFR gene, mainly substitution T790M in exon 20. Through intense research a few different mechanisms of resistance to reversible tyrosine kinase inhibitors have been identified: amplification of MET or IGF-1R genes, abnormalities of PTEN and mTOR proteins as well as rare mutations in EGFR and HER2 genes. Extensively investigated new drugs could be of significant efficiency in NSCLC patients with secondary resistance to reversible EGFR TKI.